A bolt from the blue; A case report of an unusual asthma exacerbation. (2020) - Moloney, C.; Long, A.; Pastores, G.M.; Plant, B.J.; Murphy, D.M.
Abstract: Background: We describe this case of a young gentleman presenting with acute dyspnoea on a background history of known, long-standing asthma. His dramatic presentation, notable for profound hypoxia and cyanosis, led to an unexpected additional diagnosis of type one congenital methaemoglobinaemia. Case presentation: A 26-year-old Irish gentleman was transferred urgently to the emergency department resuscitation room with marked cyanosis and tachypnoea. His oxygen saturation was 70% on 100% high flow oxygen. His arterial blood gas (On Fi02 90%) demonstrated a PaO2 = 76.8 kPa, SpO2 = 99%, pCO2 = 3 kPa and pH = 7.51. A saturation gap was evident and on further analysing the arterial blood gas, the methaemoglobin level was noted to be 28%. No contributing drugs were identified. Our patient was diagnosed with type one congenital methaemoglobinaemia. He recovered well from this admission, however, has had recurrent presentations to hospital since with high methaemoglobin levels noted on each occasion. Discussion: Congenital methemoglobinemia is a rare, often overlooked differential diagnosis in patients presenting with cyanosis and dyspnoea. This is the only case, to our knowledge, of a patient with both asthma and congenital methaemoglobinaemia. Congenital methaemoglobinaemia was first described in 1943 by Dr Deeny who described two siblings as suffering from 'Familial Idiopathic Methaemoglobinaemia'. The case we present is the first reported Irish case of congenital methaemoglobinaemia, we are aware of, since 1943. Current treatment strategies include high-flow oxygen, methylene blue infusion (contraindicated in glucose-6-phosphate-dehydrogenase deficiency) and red cell exchange transfusions in the emergency setting whilst oral ascorbic acid and riboflavin are preventative.